The consumer rights and genetically modified organisms (Revista do Tribunal Regional Federal da 3ª Região, 2013)
With the advance of science, genetic engineering has developed, which, despite the countless benefits it provides, also poses great risks to human beings. Among the advances brought about by genetic engineering are genetically modified organisms, often referred to simply as transgenics. Economic, social, ethical, scientific and environmental issues have created a great debate around these organisms, leading to the formation of two blocs of countries, one in favor and the other opposed to the release of GMOs. Legal principles have also been devised to support the position of these countries. With regard to consumer rights, the biggest controversy in the field of GMOs is the obligation to trace and label, which would guarantee consumers the right to choose whether or not to consume GM products. Therefore, given the possibilities and risks posed by GMOs, this paper will deal specifically with the relationship between the consumer's right to information and choice and the supply of genetically modified products.
Keywords: consumer rights; right to information; genetically modified organisms; transgenics; precautionary principle; principle of substantive equivalence; labeling